2016
DOI: 10.1155/2016/8696735
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Vertebral Body’s Volume as a New Parameter for Predicting the Skeletal Maturation Stages

Abstract: This study aimed to determine the correlation between the volumetric parameters derived from the images of the second, third, and fourth cervical vertebrae by using cone beam computed tomography with skeletal maturation stages and to propose a new formula for predicting skeletal maturation by using regression analysis. We obtained the estimation of skeletal maturation levels from hand-wrist radiographs and volume parameters derived from the second, third, and fourth cervical vertebrae bodies from 102 Japanese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
2
6
1
3
Order By: Relevance
“…One study 37 in the literature examined cervical vertebrae volume as a skeletal maturity index and found similar results to that of the current study, that the correlation between 2nd CVVP and MP3 stages was not statistically significant in males, whereas it was weak in females.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…One study 37 in the literature examined cervical vertebrae volume as a skeletal maturity index and found similar results to that of the current study, that the correlation between 2nd CVVP and MP3 stages was not statistically significant in males, whereas it was weak in females.…”
Section: Discussionsupporting
confidence: 88%
“…For the 3rd CVVP, the correlation was significant in both male and female groups. This result is supported by the findings of Choi et al 37 that the relatively consistent increase in maturation exists as the volume increases regarding the male and female groups.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, different authors [27][28][29][30][31][32][33][34][35][36][37] proved strong positive correlation between age and vertebral body height (anterior, posterior and middle) on lateral radiography of cervical vertebrae or vertebral volume on CT of cervical vertebrae, however, these studies were conducted on young ages <18 years to identify cervical vertebral maturation as a method of age estimation in juveniles which was different from this study.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition, many studies (Alhadlaq and Al-Maflehi, 2013; Baccetti et al, 2006Baccetti et al, , 2002Baidas, 2012;Baptista et al, 2012;Choi et al, 2016;Flores-Mir et al, 2006;Franchi et al, 2000;Mito et al, 2003Mito et al, , 2002Uysal et al, 2006) revealed that the correlation for age and vertebral body height (using cervical vertebrae lateral radiography) or vertebral volume (using CT of cervical vertebrae), was strong and positive. However, these studies used different methodologies and were conducted on younger ages below 18 in order to detect maturation of cervical vertebrae as an age determination method in juveniles, which wasn't similar to the current study.…”
Section: Discussionmentioning
confidence: 99%